Role of Land–Atmosphere Interaction in the 2016 Northeast Asia Heat Wave: Impact of Soil Moisture Initialization. Issue 2 (12th January 2023) - Yoon, Donghyuck; Kang, Taehun; Cha, Dong‐Hyun; Song, Chang‐Keun; Lee, Myong‐In; Min, Ki‐Hong; Kim, Joowan; Chun, Jong Ahn; Seo, Eunkyo
Abstract: The impact of soil moisture initialization on the 2016 Northeast Asian heat wave was explored using the Land Information System (LIS) Weather Research and Forecasting (WRF) model. To obtain advanced soil moisture estimates, various meteorological variables from the Global Data Assimilation System analysis and Integrated Multi‐Satellite Retrievals for Global Precipitation Measurement observation data were used as atmospheric forcings for the offline simulation of the Noah land surface model (Noah‐LSM). Based on the LIS, Soil Moisture Active Passive satellite were assimilated in the Noah LSM simulation. The assimilated soil moisture estimates revealed the drier land surface conditions over Northeast Asia compared with the product from the National Centers for Environmental Prediction Final Analysis (FNL) and were used as the initial condition of the WRF model. The WRF experiment initialized by the assimilated soil moisture product (LIS experiment) exhibited the observed surface air temperature (SAT) and 500 hPa geopotential height (500 GPH) over Northeast Asia compared with the result from the experiment initialized by the FNL (CTL experiment). At Week 1, the LIS experiment simulated warmer SAT than that from the CTL experiment, which was induced by the negative anomaly of latent heat flux over Mongolia. Then, 500 GPH became strong and spatially expanded in response to the thermal low induced by the warmer SAT, and the SAT was further increased during Weeks 2 and 3. Plain Language Summary: The association between soil moisture and land–atmosphere interaction occurring in the East Asia were analyzed by focusing on the 2016 extreme heat wave case. The numerical experiment with the initial soil moisture from the fusion of satellite data and land surface model output simulated a more realistic land–atmosphere interaction over East Asia within a 3‐week heat wave simulation period, compared to the experiment with the operational soil moisture product. Key Points: The soil moisture estimates assimilated by Soil Moisture Active Passive onto the offline land surface model were initialized in the Weather Research and Forecasting model Advanced soil moisture initialization represented the observed land–atmosphere interaction in the 2016 Northeast Asia heat wave